Enhancing Pedagogy and Biblical Exegesis with Emotional Intelligence - Russell Jay Hendel (Journal of Systemics, Cybernetics and Informatics)

(untitled)
In the past few decades, emotional intelligence (EI) has emerged as a competitor with ordinary intelligence (Intelligence Quotient (IQ)). The contrast is simple: IQ studies what you know; contrastively, EI studies how you relate to people. Many recent studies suggest that IQ accounts for only about 20% of success in life, with the remaining 80% being made up by other factors, emotional intelligence included. The article defines EI using a transdisciplinary approach and describes the components of EI using six rules of business email etiquette and the 7-item checklist used in the moral-legal code of Jewish law governing laws of communication. The overlap and commonality from these disparate disciplines enhances our confidence in the approach's operationality. We apply our findings to the disparate disciplines of biblical exegesis and pedagogy. Besides the traditional emphasis on tone, inclusiveness, and lack of omission and unconscious biases, the article provides some largely unexplored EI uses as a means of inferring exegesis and teaching. Consistent with the goals of this conference, we urge readers and listeners to research and apply these methods in their daily settings.